2022
DOI: 10.1021/acsnano.1c10524
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Dimensional 1D/2D van der Waals Heterojunction Diodes and Transistors in the Atomic Limit

Abstract: Inverting a semiconducting channel is the basis of all field-effect transistors. In silicon-based metal-oxide-semiconductor field-effect transistors (MOSFETs), a gate dielectric mediates this inversion. Access to inversion layers may be granted by interfacing ultrathin low-dimensional semiconductors in heterojunctions to advance device downscaling. Here we demonstrate that monolayer molybdenum disulfide (MoS2) can directly invert a single-walled semiconducting carbon nanotube (SWCNT) transistor channel without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…2D vdW materials have broad application prospects in microelectronic devices such as field-effect transistors [32,99,100], diodes [101][102][103], and basic logic circuits [104][105][106]. One of the key issues in the design of these devices is how to dissipate heat efficiently, because in many cases, smaller electronic components generate a higher density of excess heat.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…2D vdW materials have broad application prospects in microelectronic devices such as field-effect transistors [32,99,100], diodes [101][102][103], and basic logic circuits [104][105][106]. One of the key issues in the design of these devices is how to dissipate heat efficiently, because in many cases, smaller electronic components generate a higher density of excess heat.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…A highly transparent electrode has been predicted to increase the power conversion efficiency of photovoltaics and the responsivity of photodetectors . Recently, it has been reported that the gate modulation of 2D material-based electronic and optoelectronic devices can be enhanced with isolated SWCNTs and the SWCNTs in dispersion. , Compared to the 2D/2D material heterostructure, a stronger electric field could exist at the line–plane interface of MoS 2 /SWCNTs, which facilitates the charge carriers to pass through the interface . However, the 2D material-based devices with the press-transferred SWCNT film used as either an electrode or a heterostructure component have not been realized so far.…”
Section: Introductionmentioning
confidence: 99%
“…Through van der Waals force binding, a one-dimensional (1D) and a two-dimensional (2D) material can form unique mixed-dimensional heterostructures that inherit the unique physical properties of van der Waals 2D/2D heterostructures, but also have rich stack configurations, providing new manipulable freedom to adjust the structure and properties of heterostructures [ 31 , 32 , 33 , 34 , 35 , 36 ]. The versatility of heterostructure fabrication provides researchers with a new level of control over the resulting structure and properties.…”
Section: Introductionmentioning
confidence: 99%